The Congregation as a Station for Social Integration: an Analysis of Congregants’ Personal Networks with an Interpretation using Giddens’ Theory of Structuration - Stringer, Adrian (Journal of the Irish Society for the Academic Study of Religions, 2019)
This is a study of personal networks from a sample of two contrasting congregations in Northern Ireland: one is Anglican (‘A’), historic and rural, the other newly formed, independent and evangelical (‘I.E.’). This research helps to redress the lack of such studies in Britain and Ireland as compared to those in the USA. Using data from survey questionnaires and computer aided social network analysis, it investigates the role a congregation may have within such members’ networks. The findings can be broken down into four sections. First, although a substantial proportion of co-congregants formed actors’ networks, these did not form the majority of nodes. Second, Anglicans differed from the Independent Evangelical respondents in having networks of congregants who were, a) predominantly kin and b) more extensive in number. For the ‘I.E.’, the key integrative connections were provided by co-congregants. Third, congregants from both churches were primarily located within multiplex relationships - the people from their church were also either kin or already known through some other friendship group. Fourth, whilst each congregation can be differentiated from the other by social attributes (such as SEC, age, residency) such features appeared to be more that of induced homophily (local contexts and personal networks) rather than as a result of the simple agency of choice. Giddens’ Structuration Theory was found to be a useful application for the theoretical animation of these results, especially in how the congregation acts as a station for congregants, integrating the household with the meso-level of social structure.